PENGKAJIAN KEMAMPUAN TEKNOLOGI PENGOLAHAN AIR MINUM SKALA KECIL - Ruliasih Marsidi (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2003)
To fulfill the people’s primary need, the government is duty bound to stock remote regions with a steady supply of fresh water. That duty necessitates assasing and applying of appropriate water treatment system in these remote regions or villages. In fact the number of people needing the service is few, and the education level of the people is generally low. Having a small scale and simple water treatment technology would fit this standard. There are many water treatment technology, but only a few should be applied for a minimal capacity production. The applied technology should benefit the localpeople and, in accordance with local’s conditions, long-lasting. This paper will discuss various water treatment technology suitable for a small-scale production. The technologies are selected based on its ability to purify thewater and the cost of each system. The calculations were derived from otherwritten sources along with field data gathered by BPPT. These technology include the coagulation-filtration technology, slow-sand filtration technology, ion-exchange technology, reverse-osmosis technology and the active-carbon technology.